ANALYSIS INFLUENCE OF DIFFERENCE PERCEPTION BETWEEN SHARI’A BANKING WITH CONSUMER PERCEPTION TOWARDS CUSTOMER’S PURCHASE INTENSION SHARI’A BANKING IN SEMARANG – INDONESIA - Astuti, Sri Rahayu Tri (IJIBE (International Journal of Islamic Business Ethics), 2016)
Based on Shari’a Banking’s development background in  Indonesia such as phylosophy aspects, legal aspectsalso prospect and potential aspects,Shari’a Banking’s development should increase significantly. Instead of expectation, at the beginning year 2015,Shari’a Banking has decreased 1,6% inCentral Java (Jawa Tengah).This research aims to analyze influence of difference perception between Shari’a Banking with consumer perception toward customer’s purchase intention Shari’a Bankingin Semarang. This research use qualitative analysis methode with 30 respondents and this research gains :  (1)  Respondents understand and have purchase intension Shari’a Banking are 20 respondents; (2)  Respondents understand but do not have purchase intension Shari’a Banking are  4 respondents; (3)  Respondents do not understand and do not have purchase intension Shari’a Banking are 6 respondents.